Peningkatan Status Gizi Balita Melalui Meatball Euthynnus Affinis Di Puskesmas Penanae Kota Bima - zara, dea; Ningrum, Dyah Ayu Retno Ningrum; Hadijah; Nur Fitrianingsih, Nur Fitrianingsih; Fatihah, Umratul Fatihah; Aini, Qurrata Aini (Journal of Excellence Humanities and Religiosity, 2025)
The problem of malnutrition, especially underweight in toddlers, is still a serious challenge in the working area of ​​the Penanae Health Center, Bima City. This community service program aims to improve the nutritional status of toddlers with a nutritional intervention approach through the utilization of local resources, namely tuna (Euthynnus affinis), in the form of additional food (PMT) in the form of tofu fish meatballs. This activity includes an explanation of the product processing process to mothers of toddlers as well as counseling on the importance of animal protein intake and a balanced diet. The implementation method consists of three stages: preparation, implementation, and evaluation. Preparation includes coordination, recipe formulation. Implementation includes providing PMT and nutrition education to participants, while evaluation is carried out through observation of toddlers and interviews with parents regarding responses to the product. The results of the activity showed that tofu fish meatballs were well received by toddlers and parents, with a high level of acceptance in terms of taste and texture. In addition, there was an increase in the knowledge of mothers of toddlers regarding the importance of balanced nutrition. This program proves that local food-based nutrition interventions combined with community education can be an innovative and applicable solution in overcoming the problem of malnutrition in toddlers.